Production of plasticizers from waste alcohol production - Khomyn, Taras; Chobit, Maksym; Panchenko, Yuri (Lviv Polytechnic Publishing House, 2015)
The aim of this work was to study the possibility of recycling disposal alcohol production by its processing in order to obtain valuable products, namely plasticizers.
Keywords: plasticizer; fusel; esterification reaction